Recycled polyolefins waste as aggregates for lightweight concrete. (1st December 2016) - Colangelo, Francesco; Cioffi, Raffaele; Liguori, Barbara; Iucolano, Fabio
Abstract: In the present investigation polyolefin waste aggregates (PWA) obtained by recycled plastic materials were employed as substitution of natural aggregates in the manufacture of light weight aggregate concretes (LWAC). Different amounts (10, 20 and 30%) of natural aggregates were substituted by the same volume of PWA. The effect of such substitution on the main physical (porosity, density and thermal stability) and mechanical (compressive and splitting tensile strength) properties was evaluated. In addition, their post-fire residual mechanical performances were analyzed by means of density measurement, ultrasonic testing and compressive strength evaluation. The use of PWA resulted in specimens characterized by lower density and higher porosity and water absorption. Mechanical tests denote a worsening in the concrete performances with increasing of substitution, even if LWAC shows a more ductile failure under compression loading, compared to the typical brittle failure of a reference concrete. Thermal response tests performed at 600 °C indicate that compressive strength of the samples exposed to elevated temperatures are reduced considerably with the increase of percentage of the employed recycled aggregates. The addition of PWA for manufacturing of LWAC represents an opportunity to both reduce the environmental impact of plastic materials and to allow the growth of eco-sustainable building. Graphical abstract: Highlights: Polyolefin Waste Aggregates (PWA) can be successfully recycled in lightweight concrete. PWA decrease compressive strength, density and workability of lightweight concrete. Small amount of PWA, working as fibers, increases tensile strength of produced concrete.